STUDI KASUS: OPTIMISASI TEKNIK PENGADUKAN, PEMBENTUKAN GULUNGAN, DAN KEMASAN PRODUK DODOL DI KABUPATEN BEKASI - Dessy Agustina Sari; Azafilmi Hakiim; Vita Efelina; Mohammad Djaeni; Hadiyanto Hadiyanto (AGROINTEK, 2020)
Dodol is a type of food made from coconut milk, sticky rice flour, and sugar. Its main characteristic is stickiness, which becomes a difficulty during the stirring and packaging process. The need for mechanization results in the instability of production capacity. For 25 years, the core problem solving is a stainless steel material mixer with a pitch blade type that maintains the use of copper pans. This thing overcomes human strength, uniformity of dodol dough, and eliminates shifts between workers. The second is the feeding of dodol, which has been cooled to the screw extrusion rotation and results in uniform diameter of the product roll. The duration of this stage cuts the packaging time from 1-2 minutes to 26-50 seconds per dodol package (250 grams). Besides, the updating of conventional methods has been able to encourage products to reach food shops by submitting marketing authorizations at the Bekasi District Health Office. Lack of sales licenses become middlemen loopholes. Labeling production on selling products could increase the level of consumer confidence in market competition. The proximate test of dodol UKM could compete with the quality of Garut dodol.